The 20S proteasome alpha(5) subunit of Arabidopsis thaliana carries an RNase activity and interacts in planta with the Lettuce mosaic potyvirus HcPro protein - Dielen, Anne-Sophie; Sassaki, Flavio Tetsuo [UNESP]; Walter, Jocelyne; Michon, Thierry; Menard, Guillaume; Pagny, Gaelle; Krause-Sakate, Renate [UNESP]; Maia, Ivan de Godoy [UNESP]; Badaoui, Saloua; Le Gall, Olivier; Candresse, Thierry; German-Retana, Sylvie (Wiley-Blackwell, 2011)
P>In plants, the ubiquitin/26S proteasome system (UPS) plays a central role in protein degradation and is involved in many steps of defence mechanisms, regardless of the types of pathogen targeted. In addition to its proteolytic activities, the UPS ribonuclease (RNase) activity, previously detected in 20S proteasome preparations from cauliflower and sunflower (Helianthus annuus), has been shown to specifically target plant viral RNAs in vitro. In this study, we show that recombinant Arabidopsis thaliana proteasomal alpha(5) subunit expressed in Escherichia coli harbours an RNase activity that degrades Tobacco mosaic virus (TMV, Tobamovirus)- and Lettuce mosaic virus (LMV, Potyvirus)-derived RNAs in vitro. The analysis of mutated forms of the alpha(5) subunit demonstrated that mutation of a glutamic acid at position 110 affects RNase activity. Furthermore, it was demonstrated, using a bimolecular fluorescence complement assay, that the multifunctional helper component proteinase (HcPro) of LMV, already known to interfere with the 20S proteasome RNase activity in vitro, can interact in vivo with the recombinant alpha(5) subunit. Further experiments demonstrated that, in LMV-infected lettuce cells, alpha(5) is partially relocalized to HcPro-containing infection-specific inclusions. Susceptibility analyses of Arabidopsis mutants, knocked out for each At-PAE gene encoding alpha(5), showed that one (KO-pae1) of the two mutants exhibited a significantly increased susceptibility to LMV infection. Taken together, these results extend to A. thaliana alpha(5) the range of HcPro-interacting proteasomal subunits, and suggest that HcPro may modulate its associated RNase activity which may contribute to an antiviral response.